Potential of Biochar to Improve Soil Properties and Growth Performance of Oil Palm Seedlings - Chia Nin, Hwong (Universiti Malaysia Sarawak (UNIMAS), 2021)
Fertilizers are the costliest input in the oil palm plantation, losses of inorganic fertilizers are not only detrimental to the environment, but also a significant financial loss to the oil palm industry. Empty fruit bunch (EFB) and palm kernel shell (PKS) biochar are potential soil ameliorator to improve nutrient use efficiency in the oil palm plantation. Field studies were carried out to determine the effects of EFB and PKS biochar, respectively on plant growth, soil chemical properties and plant nutrient uptake of oil palm seedlings. Three rates of EFB and PKS biochar (0, 1.5 and 3%) were incorporated into the loamy sand soil for 9 months and 8 months experimental period, respectively under field condition. Oil palm seedlings at 7th month were planted in a polybag containing 15 kg dry soil and incorporated homogenously with 3 rates of EFB and PKS biochar (0, 0.225 and 0.450 kg) respectively. The experiments were arranged in a randomized complete block design(RCBD), with 3 replications. Results of the EFB biochar field study showed that the 3% biochar incorporation rate significantly (p < 0.05) improved the plant growth, biomass, soil chemical properties (CEC, available P, total P, exchangeable Ca and Mg) and plant nutrient uptake (P, Mg, Ca and B) whereas these positive effects were not observed in the PKS biochar field study. Isotope nitrogen (15N) tracing method was applied in PKS biochar field study to quantify the nitrogen up-take performance when the seedlings were 9 months old. Measurement of total plant biomass, total N and percentage N derived from fertilizer (%NdFF) were conducted during the study. The seedlings did not demonstrate any difference in nitrogen uptake with and without PKS biochar treatments. Thus, PKS biochar did not have any positive effect on nitrogen uptake. Keywords: Empty fruit bunch, palm kernel shell, soil chemical properties, nutrient uptake, isotope nitrogen (15N)